2017
DOI: 10.1038/s41598-017-16108-8
|View full text |Cite
|
Sign up to set email alerts
|

The Triglycerides and Glucose Index rather than HOMA-IR is more associated with Hypogonadism in Chinese men

Abstract: Previous studies have reported that insulin resistant and low testosterone are related. The triglyceride and glucose index (TyG) well mirrors insulin sensitivity. No study investigated the application of TyG in male hypogonadism. We aimed to explore whether TyG was associated with hypogonadism, and also evaluate the ability of TyG compared to HOMA-IR as a possible hypogonadism predictor. A total of 4299 male subjects were enrolled from 22 sites in East China. Hypogonadism was defined as total testosterone <11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
2
16
2
Order By: Relevance
“…In Brazil, Vasques et al reported better performance using the TyG index than HOMA-IR to estimate IR in Brazilian subjects [ 29 ]. Compared with HOMA-IR, several studies indicated that the TyG index was also superior at predicting carotid atherosclerosis, arterial stiffness, diabetes, and hypogonadism [ 15 , 30 32 ]. Similarly, this study found that the TyG index was more closely tied to NAFLD and liver steatosis than HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Vasques et al reported better performance using the TyG index than HOMA-IR to estimate IR in Brazilian subjects [ 29 ]. Compared with HOMA-IR, several studies indicated that the TyG index was also superior at predicting carotid atherosclerosis, arterial stiffness, diabetes, and hypogonadism [ 15 , 30 32 ]. Similarly, this study found that the TyG index was more closely tied to NAFLD and liver steatosis than HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…The results are significantly associated with the "gold standard", the glucose clamp results (4). The standard of insulin resistance index (HOMA-IR) was different in every race, every country (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we performed two parallel investigations, in normoinsulinaemic hypogonadic males and hyperinsulinaemic subjects. The two groups were selected by homeostasis model assessment of IR-index (HOMAi), the most common index to assess insulin sensitivity 14 .…”
Section: Introductionmentioning
confidence: 99%